Time and Contingency: Temporal Organization in Southern Labrador - Szala-Meneok, Karen (My University, 1992)
The aim of this dissertation is the examination of theoretlcal concepts and assumptions which have informed the study of time in cultural anthropology. In the anthropological literature, the notion of time is recognized as being a uniquely human phenomenon, having a dualistic if not paradoxical nature, that ls, it is simultaneously cyclical and lineal. These two characteristics have been viewed as being separate and opposed to each other. In this dissertation, however, I argue that they are not opposed and separate but are closely intertwined. A multidimensional helical model is employed to illustrates this interconnectedness.
I present the view that one key to understanding cyclical and linear characteristics of time can be found in examining the element of contingency. My examination of the role that contingency plays with respect to temporal organization is situated within the context of the culture of southern Labrador where contingency commands a prominent position in the lives of fishers, trappers and hunters and their families. From the ethnographic context, I address some of the important anthropological ideas that have informed the study of time and contingency in anthropology. A framework of key notions or understandings emerge from this examination, namely: (1) that time is dynamic, (2) that cyclical and lineal iii iv aspects of time are interrelated rather than opposed, (3) that time has multidimensionality and finally (4) that contingency in its various environmental and cultural expressions can effect the way in which time is conceptualized and organized. The dissertation is based on fourteen months of field research conducted in the summer of 1976, 1979-1980 and in the fall of 1988.
It begins with an examination of anthropological perspectives on the study of time and contingency. I move on 1..0 an exploration of historical and social events which provide a baseline for interpreting the relationship between contingency and time. Next, the contingencies based in the environmental cycle, particularly breakup and freezeup are explored along with adjustive responses employed by Labradorians to accommodate them.
The relationship between contingency and predictability are examined in light of work and leisure patterns of women and of men respectively. Family commensal routines provide a venue in which contingency is modulated and predictability is introduced in the daily cycle. While women and men experience different levels of contingency and predictability in their daily lives, a complementary relationship exists between male and female temporal domains. Examination of the daily cycle also reveals that the daily schedule is ordered into domains of public and private time. During ritual time, distinctions between public and private v time, between male and female, and between stranger and friend undergo symbolic inversion. Here contingencies of both the environmental and social sort are celebrated. Disguise, in the form of janneying (masking) and social drinking, provide the vehicle for such inversion. In light of t.his data, questions concerning the effect of contingent events on temporal organization are explored.
Page 114 with a diagram is actually page 116.
Page 216 with a diagram is actually page 219.
Page 224 with a diagram is actually page 227.
Page 273 with a diagram is actually page 276.
Page 295 is blank in the hard copy.
Keywords: cultural anthropology; southern Labrador; fishers; trappers; hunters; Social and Cultural Anthropology; Social and Cultural Anthropology